Effects of Added Chromium and Space Allocation on Finishing Pig Performance - A. Santos; M. D. Tokach; S. S. Dritz; J. C. Woodworth; R. D. Goodband; J. M. DeRouchey (Kansas Agricultural Experiment Station Research Reports, 2016)
A total of 256 pigs (Line 600 × 241, DNA Columbus, NE) were used in a 72-d trial to determine the effect of dietary chromium (chromium propionate; Kemin Industries, Des Moines, IA) and space allowance on performance and carcass characteristics of finishing pigs. Pens were blocked by initial weight and randomly assigned to treatments with 8 pigs per pen and 8 pens per treatment. Treatments were arranged in a 2 × 2 factorial with main effects of diet (control or added chromium, 200 ppb) and 2 space allowances (9.8 ft2- normal and 6.8 ft2– restricted). Adding chromium to the diet decreased (P = 0.044) ADG from d 56 to 72 and resulted in poorer (P = 0.021) F/G for the overall period. Space restriction decreased (P<0.001) ADG and ADFI for all periods within the study and final BW, and HCW, but increased (P = 0.009) carcass yield and decreased (P = 0.003) backfat depth. These results indicate that chromium propionate did not improve performance when pigs were restricted in space.
Keywords: chromium propionate; finishing pig; stocking density